TELAAH KRITIS ATAS SISTEM PEMIDANAAN IN ABSTRACTO DAN IMPLIKASINYA DALAM PENEGAKKAN HUKUM PIDANA DI INDONESIA - Tongat S.H., M.H. (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2013)
One of the acute problems of criminal law enforcement in Indonesia in abstracto stages that are not determined the purpose of punishment in the criminal system. In the views that way, so burst practical implications. Messy criminal law enforcement in Indonesia leads to deficiencies and weaknesses that criminal system. Although not a single variable, shortcomings and weaknesses to